KOMPETENSI PENYULUH PERTANIAN TERHADAP PENGEMBANGAN GOOD AGRICULTURAL PRACTICES (GAP) HORTIKULTURA DI PROVINSI BANGKA BELITUNG - Rostiar Sitorus, Silfina Puteri, Muntoro dan (LPPM UBB, 2014)
ABSTRACTThe purpose of this study is to describe the implementation of GAP, extension system characteristics, and the determinant factors that affect the competency of agricultural extension to GAP development ofhorticulture in Bangka Belitung Province. The data processed using analysis correlation coefficient analysis kendalls tau-b (r) and multiple linear regression analysis. The results showed that (1) Implementation of GAP at three district study sites have not been going well because it is still hampered by various obstacles, such as the budget for training, technical knowledge about cultivation GAP extension and farmer mindset that says that according to the GAP farming costs expensive and long harvest age, (2) Characteristics of the extension system involves aspects of quantity and quality of inadequate extension 1 extension 1 village, as well as technical knowledge in accordance with GAP cultivation of plants is still low, which is done by the extension method in extension activities extensionis not GAP GAP appropriate so that development has not been achieved, (3) internal factors and external factors that affect the level of competency of agricultural extension in the development of GAP with the 95% confidence level is kekosmopolitan (X1.4), organizational structure (X2.1) and the support means (X2.3).Keywords: Competence, Agricultural Extension, Good Agricultural Practices